Journal of Earth System Science Published by the Indian Academy of Sciences - Chalapathi Rao, N V.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer.)
Begun in 1934, the Proceedings of the Indian Academy of Sciences (Earth and Planetary Sciences) was a quarterly journal. Renamed Journal of Earth System Science in 2005, the journal is now published bimonthly. The journal is highly interdisciplinary and publishes high-quality research - new data, ideas, and conceptual advances - in Earth System Science in its broadest sense. This includes the solid earth, the atmosphere, the hydrosphere, and the biosphere; it also addresses related aspects of planetary and space sciences. Contributions pertaining to the Indian subcontinent and the surrounding Indian Ocean region are particularly welcome.
Keywords: Earth sciences; Space sciences; Earth Sciences, general; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics) .